In its very early phases, COVID-19 shifts the associations between alcohol consumption and psychological symptoms in young adults - Janson, Karina; Bokde, Arun L. W.; Desrivières, Sylvane; Garavan, Hugh; Gowland, Penny; Grigis, Antoine; Heinz, Andreas; Martinot, Jean-Luc; Paillère Martinot, Marie-Laure; Artiges, Eric; Orfanos, Dimitri Papadopoulos; Paus, Tomáš; et al. (European psychiatry, 2025)
BackgroundThe COVID-19 pandemic has impacted various aspects of daily life, leading to increased psychological symptoms and changes in alcohol use, yet little is known about their specific interactions, particularly early stages during the pandemic. We examined the relationship between psychological symptoms and alcohol-related behaviors associated with COVID-19, and determined whether associations shifted already early during the pandemic and whether changes in psychological symptoms from the pre- to during COVID-19 impacted changes in alcohol consumption.MethodsParticipants were young adults from a longitudinal cohort (N=435, age: 22-25) from two time points. We applied paired samples t-tests, correlation analyses, SHapley Additive exPlanations, and classification models to examine the multiple associations between psychological symptoms and alcohol use directly pre- and early during COVID-19.ResultsWe found significant associations between psychological symptoms and alcohol use pre- compared to during COVID-19. Anxiety was the strongest factor influencing alcohol use pre-pandemic, depression had the greatest impact during COVID-19. Changes in anxiety from pre- to during COVID-19 were the main factor associated with an increase in alcohol use, while changes in depression appeared to be most predictive for a decrease/persistence in alcohol use.ConclusionThese findings suggest a shift in the association between psychological symptoms and alcohol use following COVID-19, as well as a differential impact of psychological symptoms, depending on their changes related to the pandemic. Changes in anxiety may contribute to riskier alcohol use behaviors following the pandemic, while depression appears to be one of the most critical factors influencing alcohol use during such crisis situations.